Les comédiens itinérants à Bruxelles au XVIIIe siècle - Van Aelbrouck, Jean-Philippe (Etudes sur le XVIIIe siècle series, 2022)
The history and life of traveling troupes in the 18th century has been the subject of numerous monographs, all focusing on a particular aspect, a town or, more rarely, a region.